Notions and expectations related to work and jobs among first year university students - Nagy, Adrian; Liskuné Vathy, Veronika (Wyobrażenia i oczekiwania związane z pracą i zatrudnieniem wśród studentów pierwszego roku, 2019)
Demands concerning the labor market in Hungary tend to change these days faster than ever. It can be seen even in the plans and expectations of students enrolled in higher education institutions. In our research project, we have tried to find answers to the following questions: What kind of work experience did students have when they started their university studies in the 2019/2020 academic year? What jobs do they foresee for themselves in the future? What kind of salary do they expect to get for this, and what sort of considerations and persons influence them in the process of choosing a workplace? Furthermore, do they wish to live and work in Hungary or in another country? During the course of our survey, we used a questionnaire, for the analysis of which we completed correlation analyses and cross-tab(ulation) analyses among other things. After the evaluation of the findings and results, we may state that the majority of the students in the sample do have some work experience. Furthermore, the criteria influencing their choice of work(place) are also presented
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 4, s. 55-72
Keywords: higher education; employment; workplace; salary; studia; zatrudnienie; miejsce pracy; wynagrodzenie